2016
DOI: 10.1148/radiol.2015151256
|View full text |Cite|
|
Sign up to set email alerts
|

Potential Utility of a Combined Approach with US and MR Arthrography to Image Medial Elbow Pain in Baseball Players

Abstract: Purpose To evaluate a combined imaging approach with both ultrasonography (US; conventional US and valgus stress US) and magnetic resonance (MR) arthrography in baseball players with medial elbow pain. Materials and Methods Institutional review board approval was obtained and the requirement for informed consent was waived. The study is compliant with HIPAA. Baseball players with medial elbow pain underwent US in addition to MR arthrography. Findings were assessed with each modality alone and both combined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Ciccotti et al 2 indicated that the use of stress US can detect changes to the UCL in asymptomatic professional baseball pitchers. More recently Roedle et al 5 concluded that that conventional US is as accurate as MR arthrography in diagnosing UCL tears. An emerging feature of MSKUI is Power Doppler imaging quantification (PDIQ) that can be used to quantify circulation in MSK tissues and provide a measure of tissue perfusion and/or inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Ciccotti et al 2 indicated that the use of stress US can detect changes to the UCL in asymptomatic professional baseball pitchers. More recently Roedle et al 5 concluded that that conventional US is as accurate as MR arthrography in diagnosing UCL tears. An emerging feature of MSKUI is Power Doppler imaging quantification (PDIQ) that can be used to quantify circulation in MSK tissues and provide a measure of tissue perfusion and/or inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In cases not responding to these treatments, surgical release of the tendons can be performed (121). A recent study has shown that the combination of MR arthrography and US is highly accurate for assessment of elbow pain in athletes (122). Similarly, we believe that US and MR arthrography are complementary for evaluation and image-guided treatment of hip disease.…”
Section: Snapping Hip Syndromementioning
confidence: 99%
“…The ulnar collateral ligament is evaluated dynamically with ultrasound and complements MR arthrography where the accuracy in diagnosis of tear is highest when both imaging methods are used [20]. With the elbow flexed at least 30°, valgus stress is placed across the elbow.…”
Section: Elbowmentioning
confidence: 99%
“…With the elbow flexed at least 30°, valgus stress is placed across the elbow. Asymmetric widening of the medial joint space between the humerus and ulna with valgus stress can indicate ligament tear [20]. The ulnar nerve can also be imaged by dynamic ultrasound to assess for injury or subluxation.…”
Section: Elbowmentioning
confidence: 99%